Markets and Policy Measures in the Evolution of Electric Mobility - Fornahl, Dirk; Hülsmann, Michael (Lecture Notes in Mobility, 2016)
This edited monograph collects theoretical, empirical and political contributions from different fields, focusing on the commercial launch of electric mobility, and intending to shed more light on the complexity of supply and demand. It is an ongoing discussion, both in the public as well as in academia, whether or not electric mobility is capable of gaining a considerable market share in the near future. The target audience primarily comprises researchers and practitioners in the field, but the book may also be beneficial for graduate students.